Psychoeducation program â€œMe and Marriage: Marriage with Preparationâ€ as a prevention of early marriage - Vidya Anindhita; Hendriati Agustiani; Langgersari Elsari Novianti; Ajeng Nuranti Syafitri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Commitment to a romantic relationship is a developmental task of early adulthood that usually manifests as marriage. The government has established a minimum age of marriage for both men and women. Nonetheless, specific regions in West Java still witness marriages of couples under this prescribed age when early marriage can bring difficulties for young couples adjusting their roles as husband or wife, parents, and partaking in childcare and conflict resolution. This issue is evident in Cipacing, Jatinangor, with many instances of adolescent marriages, child stunting cases, and adolescents committing risky behaviors. Thus, the present Community Engagement (PPM) program aims to provide knowledge and awareness for adolescents and early adults regarding the significance of preparatory measures before marriage. The activity focuses on educating the meaning of marriage, essential premarital preparations, and self-identification related to marriage readiness. A total of 40 adolescents and early adults participated in the activity. Our analysis of pre-and post-test scores revealed improved mean scores by a majority of participants, indicating increased knowledge. Recommendations for future activities include optimizing the socialization process by adopting a more concise timeframe and employing a delivery method that ensures ease of comprehension, allowing the next program to run more efficiently and effectively.